The Impact Of The National Credit Act On Residential Mortgage Lending In South Africa - Boonzaaier, Catherine; Chisasa, Joseph (Journal of Applied Business Research, 2018)
The purpose of the study reported in this article was to determine the impact of the National Credit Act on residential mortgage lending in South Africa. The National Credit Act (NCA) was promulgated and implemented on 1 June 2007. The purpose of the NCA was to remove the many unfair practices, inappropriate disclosure and anti-competitive practices from the market and to achieve honesty in the credit market. Low-income groups were held back because they could not gain access to formal finance to build or improve houses or supplement housing subsidies to get bigger houses. This study applied a quantitative research design using monthly time series secondary data for the period January 2001 to August 2011. The statistical analysis techniques used in this study were t-tests, descriptive statistics, trend analysis and correlation analysis. It was found that the NCA had a positive effect on the residential mortgages in South Africa. These results have policy implications on the continued regulation of the credit market and the avoidance of reckless lending.